MODIFIED SMECTITIC TUNISIAN CLAYS USED IN THE FORMULATION OF HIGH PERFORMANCE LUBRICATING GREASES - Chtourou M.; Frikha M.H.; Trabelsi M. (My University, 2006)
Two smectitic Tunisian clays were organically modified by exchange reaction with dioctadecyl dimethylammonium chloride (DODMA) and hexadecyl benzyl dimethylammonium chloride (HBDMA). The resulting organoclays were used in the formulation of lubricating greases. The results of the performance tests applied to the obtained greases showed that their physicochemical and mechanical characteristics are in conformity with the extreme-pressure (EP) greases specifications. The obtained greases present good EP properties with only 0.5% EP additives. The smectitic clays used could constitute a raw material in the formulation of high performance lubricating greases. © 2006 Elsevier B.V. All rights reserved.
Keywords: EXTREME-PRESSURE GREASES; ORGANOCLAY; SMECTITE; TUNISIAN CLAYS